2021
DOI: 10.1016/j.ijso.2021.100322
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative risk stratification and strategies for reducing postoperative pulmonary complications following major surgery in resource limited areas: A systematic review

Abstract: Background: Postoperative pulmonary complication can be broadly defined as conditions affecting the respiratory tract that can adversely influence the clinical course of a patient after surgery. Post-operative pulmonary complications are the most frequent reported cause of morbidity and mortality in hospitals. The occurrence of postoperative pulmonary complications in the world is between 5 and 80% with variation attributed to set-up, preoperative and intra-operative risk factors. The incidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…It is essential to screen patients for their risk of PPCs preoperatively to customize preventive strategies 5,6 . Pfeifer indicated that this risk assessment is essential because perioperative teams do not have the time or resources to provide every potential risk reduction intervention to every patient.…”
Section: Evaluating Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…It is essential to screen patients for their risk of PPCs preoperatively to customize preventive strategies 5,6 . Pfeifer indicated that this risk assessment is essential because perioperative teams do not have the time or resources to provide every potential risk reduction intervention to every patient.…”
Section: Evaluating Riskmentioning
confidence: 99%
“…It is essential to screen patients for their risk of PPCs preoperatively to customize preventive strategies. 5,6 Pfeifer indicated that this risk assessment is essential because perioperative teams do not have the time or resources to provide every potential risk reduction intervention to every patient. "It is important to identify risk in as objective a manner as possible, so that you can efficiently utilize your resources on the patients most likely to benefit: those who are at least at intermediate, if not high, risk for pulmonary complications," he said.…”
Section: Evaluating Riskmentioning
confidence: 99%
See 1 more Smart Citation